Formation of Gas Hydrates at Deep Interior of the Earth and Their Dissipation to Near Surface Horizon. (10th December 2013) - Ramasamy, Ramachandran; Subramanian, Subramanian; Sundaravadivelu, Ranganathan
Abstract : Methane hydrates occur in diverse geological settings and their origin is puzzling, owing to package of more than 160 times of equivalent volume of methane in ice cage at standard temperature pressure indicating formation at high pressure state. At the core mantle boundary of the Earth, high dense supercritical fluids of Fe with significant amount of O, Ti, Nb, C, H, and other elements exist. Geophysical studies reveal that at the core mantle boundary of the Earth at 2900 km depth, temperature exceeds 4000°C, pressure ranges around 135 GPa and the material present possesses high molar volume 8.8 gm/cm 3 . Sudden release of pressure causes opening of vents and supercritical fluid/plasma phase of CH4 exsolves as finely divided plasma bubbles and rapidly rises up through weak planes. The potential energy of these bubbles is so high; the velocity of ascending bubbles steadily increases with super adiabatic state with minimum frictional energy loss. The rapidly ascending CH4 plasma bubbles quench with outer skins of H2 or H2 O while passing through the permafrost or near surface horizons. Again, some bubbles burst into numerous tiny droplets of dense methane into cold seawater near seafloor. The water layer surrounding the tiny bubble is formed as ice-cage on hydrophobic methane, by absorbing or releasing sufficient latent heat energy from freezing water for endothermic formation of methane hydrate. The water envelops as ice cage around CH4 near surface conditions at ambient temperature and pressure conditions. Numerical analyses of specific heats J/mole for CH4 and H2 O reveal that such plasma bubbles could form even from upper mantle horizons ~100 km depth but with less potentiality. The charged particles inside the plasma bubble are highly influenced by magnetic and electric fields. Hence most bubbles drive through deep interconnecting fractures towards continental margins of polar region where earth's electromagnetic and gravity intensities are relatively high.